2014
DOI: 10.6060/mhc140719s
|View full text |Cite
|
Sign up to set email alerts
|

Pillar[5]arenes with Morpholide and Pyrrolidide Substituents: Synthesis and Complex Formation with Alkali Metal Ions

Abstract: Novel pillar [5]arenes containing morpholide and pyrrolidide were synthesized by step-by-step functionalization of the perhydroxylated pillar [5]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 19 publications
(42 reference statements)
3
14
0
Order By: Relevance
“…This differs from the group's observation of selectivity for Na + and K + with 1 , however, when immobilised in carbon paste that macrocycle is unable to rotate around its methylene bridges and cannot adopt a suitable coordination environment for Li + . When attached to the gold surface through thiols on one ring the remaining rings can rotate to bind partially dehydrated Li + in a tetrahedral or octahedral environment in agreement with the findings of Stoikov . The group used the same pillar[5]arene derivative to target the biogenic amines putrescine, spermidine and spermine .…”
Section: Pillar[n]arenes For Detectionsupporting
confidence: 69%
See 1 more Smart Citation
“…This differs from the group's observation of selectivity for Na + and K + with 1 , however, when immobilised in carbon paste that macrocycle is unable to rotate around its methylene bridges and cannot adopt a suitable coordination environment for Li + . When attached to the gold surface through thiols on one ring the remaining rings can rotate to bind partially dehydrated Li + in a tetrahedral or octahedral environment in agreement with the findings of Stoikov . The group used the same pillar[5]arene derivative to target the biogenic amines putrescine, spermidine and spermine .…”
Section: Pillar[n]arenes For Detectionsupporting
confidence: 69%
“…Na + could be monitored in the 4×10 −2 to 0.2 M range and a limit of detection of 4.1×10 −2 M. This was within the clinical range for the analyte whereas for K + , while the sensitivity was slightly greater, the limit of detection was 2.28×10 −3 M and above the lowest physiological concentration encountered. Similar selectivity was observed spectroscopically for pyrrolidino‐ and morpholinopillar[5]arene derivatives 26 and 27 (Figure ) reported by Stoikov and colleagues, although greatest selectivity was for Li + . Following the discovery by Chen, Hou and colleagues that 3 could form ‘water wires’, Cragg and colleagues incorporated the macrocycle in an ion‐selective electrode and measured the change in potential from pH 1 to 4 .…”
Section: Pillar[n]arenes For Detectionsupporting
confidence: 65%
“…The 4,8,14,18,23,26,28,31,32,35‐deca(carboxymethoxy)pillar[5]arene (P[5]A‐COOH) (see Figure S2 of Supporting Information) was synthesized from the unsubstituted pillar[5]arene as described elsewhere at the Organic Chemistry Department of Kazan Federal University. Briefly, etherification with ethyl bromoacetate in acetonitrile was used with the following hydrolysis of esteric groups by KOH in aqueous tetrahydrofuran (THF).…”
Section: Methodsmentioning
confidence: 99%
“…Pillar [5]arenes 3-7 were synthesized by literature method. [23,28] General procedure of the synthesis of the compound 8. To deca(carboxymethoxy)pillar [5]arene [23] (0.30 g, 0.25 mmol) in a round bottom flask, 10 ml (84 mmol) of SOCl 2 and catalytic amount of DMF were added.…”
Section: Synthesesmentioning
confidence: 99%
“…Earlier in our research group, [21][22][23][24][25][26] it was shown that the functionalization of the pillar [5]arene with amide fragments increases the solubility of compounds in water and promotes self-association and aggregation of the resulting macrocycles. So, we proposed approach to the introduction of ten amide fragments into the pillar [5]arene structure for the purpose of selective recognition of metal ions, by varying the substituents in the amide fragment (-C(O)-NH-R and -C(O)-NR 2 ).…”
Section: Introductionmentioning
confidence: 98%